Diversity of biological activities of crude venom extracted from five species of South China Sea anemones - He, Panmin; Li, Ming; Fu, Jinxing; Liao, Yanling; Yi, Bo; Gao, Bingmiao (Frontiers in Marine Science, 2024)
Developing novel, efficient, and safe peptide drugs from sea anemones has aroused great interest in countries around the world today. Sea anemones contain complex protein and peptide toxins, which determine the diversity of their biological activities. In this study, a variety of activities were assessed for crude venom extracted from five species of South China Sea anemones, including hemolytic, enzyme inhibition, anticancer, insecticidal, analgesic and lethal activities. The most toxic sea anemone was found to be Heteractis magnifica, which has high lethal activity in mice with an LD50 of 11.0 mg/kg. The crude venom of H. magnifica also exhibited a range of the most potent activities, including hemolytic, trypsin inhibitory, cytotoxic activity against U251 and A549 cells, insecticidal and analgesic activities. In addition, the crude venom of Stichodactyla haddoni was the most effective inhibitor of pepsin, and the crude venom of Heteractis crispa was extremely strong toxicity to HepG2 cells. These findings are of great significance for exploring the potential and application of South China Sea anemone resources, and are expected to provide new directions and possibilities for the development of novel anticancer drugs, analgesics and biopesticides.